The Quintessence of Strategic Management What You Really Need to Know to Survive in Business - Kotler, Philip; Berger, Roland; Bickhoff, Nils (Quintessence Series, 2016)
This book provides practitioners with a basic understanding of strategy and the process of strategic management. Using academic foundations and best practices from business life, the authors present the most important strategy tools and how they interact. The book gives a concise overview over the focal areas and considerations of strategy in practice. It enables managers to analyze and interpret buisness information with regard to the underlying strategic notions. A hands-on introduction to strategic management by leading marketing authority Philip Kotler, top management consultancy founder Roland Berger, and strategy expert Nils Bickhoff.